South Korea's Public Diplomacy in Indonesia Through the Korea Week Program in 2023 - Wirayuda, Hansen; Ningtias, Kartika; Alunaza, Hardi (Prodi Hubungan Internasional Program Magister Univ. Muhammadiyah Yogyakarta, 2026)
This study analyses the implementation of integrated public diplomacy through the Korea Week 2023 program in Indonesia within the framework of a middle-power state. The study utilises the five elements of public diplomacy identified by Nicholas J. Cull: listening, advocacy, cultural diplomacy, exchange diplomacy, and international broadcasting, employing a qualitative descriptive approach based on secondary sources. The findings indicated that Korea Week does not focus on creating new cultural appeal, but rather on consolidating existing soft power. The practice of listening capitalises on the high level of enthusiasm among the Indonesian public for Korean culture. Advocacy is integrated into economic and digital forums. Cultural diplomacy is realised through performances and culinary activities. Exchange diplomacy encourages active participation, whilst international broadcasting expands reach through digital media. The integration of these five elements demonstrates a middle-power state's ability to transform popularity into sustainable diplomatic capital. This study confirmed that event-based diplomacy can function as a strategy for managing soft power, rather than merely as image projection. These findings also indicate that diplomatic influence is maintained through the synchronisation of culture, policy, and narrative, thereby strengthening legitimacy and strategic partnerships without coercion.